Efektifitas Pijat Batuk Pilek pada Balita di Desa Morangan Kecamatan Suruh - Pertiwi, Saskia Inggar; Dewi Setiyani; Ninik Christiani; Heni Setyowati (Universitas Ngudi Waluyo, 2024)
Children and toddlers are a group of people who are more susceptible to coughs and colds. This is caused by the weak immune system of children and toddlers. A typical toddler in Indonesia is estimated to have cough and cold symptoms 3 to 6 times per year, which on average consists of 3 to 6 episodes. Children are more susceptible to coughs and colds that develop into pneumonia, which is promoted by unclean environmental conditions and excessive air pollution. (Purnama, 2018). additional therapy that can relieve coughs and colds. Infant and toddler massage can increase a child's weight, accelerate neuromotor development, improve emotional relationships, and reduce the rate of nosocomial infections (Kulkarni et al., 2010). The target in this activity is mothers who have toddlers, a sample of 21 toddlers. The media used in this community service are power point and video. The results of the experimental group analysis using the T test with the results of knowledge based on age being 0.754 and knowledge based on education being 0.003, it can be concluded that there is no relationship between knowledge and mother's age and there is a relationship between knowledge based on education level. The results of the experimental group analysis using the T test with the results of knowledge based on age being 0.754 and knowledge based on education being 0.003, it can be concluded that there is no relationship between knowledge and mother's age and there is a relationship between knowledge based on education level. there is a significant difference after the pre-test and post-test, namely there is an increase in the mother's knowledge and skills regarding the benefits of massage for coughs and colds. Abstrak Anak-anak dan balita adalah sekelompok orang yang lebih rentan terhadap batuk pilek. Hal ini disebabkan oleh sistem kekebalan tubuh anak-anak dan balita yang masih lemah. Balita tipikal di Indonesia diperkirakan memiliki gejala batuk pilek 3 hingga 6 kali per tahun, yang rata-rata terdiri dari 3 hingga 6 episode. Anak-anak lebih rentan terhadap batuk pilek yang berkembang menjadi pneumonia, yang dipromosikan oleh kondisi lingkungan yang tidak bersih dan polusi udara yang berlebihan. (Purnama, 2018). Terapi tambahan yang dapat meringankan batuk pilek. Pijat bayi dan balita dapat meningkatkan berat badan anak, mempercepat perkembangan neuromotorik, meningkatkan hubungan emosional, dan mengurangi tingkat infeksi nosocomial (Kulkarni et al., 2010). Sasaran dalam kegiatan ini adalah ibu yang memiliki balita, sampel 21 balita, Media yang digunakan dalam pengabdian masyarakat ini adalah power point dan video. Hasil analisis kelompok eksperimen dengan uji T dengan hasil pengetahuan berdasarkan umur 0.754 dan pengetahuan berdasarkan pendidikan 0.003 , maka dapat disimpulkan bahwa tidak ada hubungan pengetahuan dengan umur ibu dan ada hubungan pengetahuan berdasarkan tingkat Pendidikan terdapat perbedaan yang signifikan setelah dilakukan pre test dan postest yaitu terdapat peningkatan pegetahuan dan keterampilan ibu mengenai manfaat pemijatan batuk pilek